Removal of Ship Skeleton Based on Ratification of Nairobi International Convention on The Removal of Wrecks 2007 in Indonesia - Benyamin Ricchi Arcinius; Nanda Dwi Rizkia; Hardi Fardiansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
To improve ship safety, especially in overcoming the potential danger of ship skeletons, Indonesia through the Ministry of Transportation has ratified the Nairobi International Convention on the Removal of Ship Skeletons, 2007 (Nairobi International Convention on The Removal of Wrecks, 2007) with Presidential Regulation No. Republic of Indonesia. 80 of 2020 Ratification of the Nairobi International Convention on The Removal of Wrecks, 2007 (Nairobi International Convention About the Removal of Ship Framework, 2007) was signed in Jakarta on 20 July 2020 by the President of the Republic of Indonesia Joko Widodo. The research method uses normative legal research methods, a process to identify legal rules, legal principles and legal doctrine, to answer legal questions faced